Sensory, olfactometry and comprehensive two-dimension algas chromatography analyses as appropriate tools to characterize the effects of vine management on wine aroma. - NICOLLI, K. P. (2017)
For the first time, the influence of different vine management was evaluated in relation to volatile profile and sensory perception through GC×GC/TOFMS, QDA, GC-FID, GC/MS, and GC-O.GC×GC/TOFMS analyses and QDA have shown that a larger spacing between vine rows (2 rather than 1 m),attachment of shoots upwards, and irrigation did not result in wine improvement. Conversely,wines elaborated with grapes from a vine with a lower bud load (20 per plant; sample M 1) stood out among the other procedures, rendering the most promising wine aroma.GC×GC/TOFMS allowed identification of 220 compounds including 26 aroma active compounds also distinguished by GC-O.